Inter-individual differences in muscle damage following a single bout of high-intense whole-body electromyostimulation - Teschler, Marc; Waranski, Melina; Schmitz, Boris; Mooren, Frank C. (Frontiers in Sports and Active Living, 2024)
Purpose This brief report aimed to characterize inter-individual training responses following a single session of high-intense whole-body electromyostimulation (WB-EMS) using markers of muscle damage over a period of 72 h. Methods Twelve healthy individuals (5 men, 7 women; 32.0 ± 7 years) participated in a single 20-minute high-intensity WB-EMS training session. Markers of muscle damage, creatine kinase (CK) and myoglobin (Mb), were assessed before and immediately after training, as well as at 1.5, 3, 24, 48 and 72 h post-exercise. Lactate levels were determined pre- and post-exercise. Results Overall, WB-EMS induced significant CK elevations, peaking at 72 h (18.358 ± 21.380 U/L; p < 0.01), and correlating Mb levels peaking at 48 h (1.509 ± 1.394 ng/dl, p < 0.01). Despite significant inter-individual variability in CK levels, both slow (SR) and fast responders (FR) were identified. FR showed significant increases in CK at all time points post WB-EMS (p < 0.05), whereas CK in SR significantly elevated after 48 h. Post-WB-EMS lactate concentration was identified to predict peak CK and Mb levels (r ≥ 0.65, both p < 0.05). Conclusion High-intensity WB-EMS has the potential to induce severe muscle damage, as indicated by elevated levels of CK and Mb. We identified two distinct groups of individuals, SR and FR, indicating variability in response to WB-EMS. Furthermore, we suggest that individual responses to WB-EMS can be predicted based on post-WB-EMS lactate concentration.